Topical dorzolamide for macular edema in the early phase after vitrectomy and epiretinal membrane removal - Suzuki T (Dove Medical Press, 2013)
Takahiro Suzuki, Kenji Hayakawa, Yoshihiro Nakagawa, Hiromi Onouchi, Masafumi Ogata, Kenji KawaiDepartment of Ophthalmology, Tokai University School of Medicine, Isehara, JapanBackground: The purpose of this study was to evaluate prospectively the efficacy of a topical carbonic anhydrase inhibitor in macular edema after vitrectomy.Methods: Forty patients were included, all of whom had undergone vitrectomy combined with phacoemulsification and intraocular lens implantation for epiretinal membrane. Twenty eyes from 40 patients received topical 2% dorzolamide three times a day. The patients were followed up for at least 3 months. In this study, we evaluated the effect of dorzolamide on visual acuity, intraocular pressure, central macular thickness, and aqueous flare.Results: Mean logarithm of the minimum angle of resolution (logMAR) best-corrected visual acuity preoperatively and 2 weeks, 1 month, and 3 months after surgery was 0.48 ± 0.23, 0.60 ± 0.16, 0.40 ± 0.29, and 0.24 ± 0.32, respectively, in the treatment group, and 0.40 ± 0.09, 0.44 ± 0.12, 0.32 ± 0.10, and 0.16 ± 0.09, respectively, in the control group. No statistically significant difference was observed between the two groups. Mean central macular thickness preoperatively and at 2 weeks and 3 months after surgery was 572.6, 427.2, and 333.4 µm, respectively, in the treatment group, and 571.4, 485.2, and 388.4 µm, respectively, in the control group. Mean aqueous flare preoperatively, and 1 month and 3 months after surgery was 8.6, 34.2, and 23.5 photon counts per millisecond (pc/ms), respectively, in the treatment group, and 9.7, 24.7, and 23.4 pc/ms, respectively, in the control group. No statistically significant differences were observed between data from the two groups. However, statistically significant (P < 0.05) differences in mean central macular thickness at 1 month and mean aqueous flare at 2 weeks after surgery were found between the treatment group (358.8 µm, 36.8 pc/ms) and the control group (467.8 µm, 64.0 pc/ms). Differences in mean intraocular pressure preoperatively and at 2 weeks, 1 month, and 3 months after surgery were not statistically significant between the two groups. Intraocular pressure never exceeded 21 mmHg.Conclusion: Topical dorzolamide significantly reduced mean central macular thickness at 1 month and mean aqueous flare at 2 weeks after surgery for epiretinal membrane compared with controls. Although further investigation of more cases and longer follow-up are needed, this study suggests that topical dorzolamide can be efficacious in reducing macular edema in the early phase after vitrectomy via its anti-inflammatory effect.Keywords: macular edema, dorzolamide, epiretinal membrane, vitrectomy, anti-inflammatory